Doodle bites - Dunbar, Polly (Walker London, 2010)
Doodle is feeling bitey. And what better to bite than a big bottom - Tumpty's. Poor, sore Tumpty is so upset he stamps on Doodle's tail, and now both of them are upset, and before long everyone is upset! When Doodle and Tumpty apologise, everyone can be happy again. But Doodle is still feeling just a little bit bitey. Ages 3+